8 - Workplace Hazards and Social Positioning Efforts of Male Adolescent Labourers in Suburb Sawmills, Lagos State Nigeria - Ojo Melvin Agunbiade, (African Sociological Review, 2015)
Young people with low socioeconomic background require resilience to survive in a city with limited opportunities. Unintendedly such efforts sometimes affect their well-being. Such is the case of adolescent dwelling in some urban suburbs across cultures. Based on sixteen faceto- face interviews with adolescent boys working as labourers in suburb sawmills; this paper situates the notion of boyhood and survival into adulthood within a social space. The findings revealed conscious absorption with the notion of boyhood through certain rules of engagement and survival measures. These strategies include self-care practices geared towards achieving a healthy body for contextualised performance in the factory settings. However, this comes with series of consequences as boys lived out the social notions of boyhood and rules of engagement in activities for survival and social recognition. Hence, understanding and targeting the positive survival strategies of this social category of adolescents could be useful to empower and minimise the hazards of working and growing as adolescents in the physical and social spaces of sawmills.